2022
DOI: 10.7189/jogh.12.04019
|View full text |Cite
|
Sign up to set email alerts
|

Quality of routine health facility data used for newborn indicators in low- and middle-income countries: A systematic review

Abstract: Background High-quality data are fundamental for effective monitoring of newborn morbidity and mortality, particularly in high burden low- and middle-income countries (LMIC). Methods We conducted a systematic review on the quality of routine health facility data used for newborn indicators in LMIC, including measures employed. Five databases were searched from inception to February 2021 for relevant observational studies (excluding case-control studies, case series, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…14 This is because the data can be incomplete, difficult to access, and expensive to extract and process. 15 16 Most studies conduct one-off subnational surveys to collect data 17 18 or rely on national household surveys such as the Demographic and Health Survey. 19 20 However, surveys can be expensive and infrequent.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…14 This is because the data can be incomplete, difficult to access, and expensive to extract and process. 15 16 Most studies conduct one-off subnational surveys to collect data 17 18 or rely on national household surveys such as the Demographic and Health Survey. 19 20 However, surveys can be expensive and infrequent.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…There is a paucity of studies using routine health data to evaluate the relationship between quality maternal healthcare and birthing service utilisation 14. This is because the data can be incomplete, difficult to access, and expensive to extract and process 15 16. Most studies conduct one-off subnational surveys to collect data17 18 or rely on national household surveys such as the Demographic and Health Survey 19 20.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of adequate filing systems and the incomplete or contradictory information that many of the sets of notes in this study contained, is likely to impact efforts to improve the quality of patient care, both directly as complete medical history is not available and through difficulty in conducting clinical audit and research [12].…”
Section: Poor Quality Of Recordsmentioning
confidence: 99%
“…In the same study, only 6.7% indicators were found meeting all requirements for scientific soundness [7]. Systematic review of maternal and newborn data from 34 studies highlighted heterogeneity [8]. poor skills are all shown to be linked issues [11].…”
Section: Introductionmentioning
confidence: 99%
“…Once data are reported with poor quality, they contribute to inadequate decisions taken at different levels, causes insufiscient confidence in health systems, and result in non-validity of impact evaluation studies. Findings from 34 studies in published literature evaluated the quality of newborn data collected at health facility level in LMIC, revealed that there is no study reporting on the quality of newborn indicators and the systematic review done highlighted heterogeneity [17]. In Rwanda, maternal health related data was over-reported more than other indicators [18].…”
Section: Introductionmentioning
confidence: 99%